Salmonella enterica induces and subverts the plant immune system - Garcia, Ana V.; Hirt, Heribert (Frontiers in Microbiology, 2014)
Infections with Salmonella enterica belong to the most prominent causes of food poisoning and infected fruits and vegetables represent important vectors for salmonellosis. Whereas it was shown that plants raise defense responses against Salmonella, these bacteria persist and proliferate in various plant tissues. Recent reports shed light into the molecular interaction between plants and Salmonella, highlighting the defense pathways induced and the means used by the bacteria to escape the plant immune system and accomplish colonization. It was recently shown that plants detect Salmonella pathogen-associated molecular patterns (PAMPs), such as the flagellin peptide flg22, and activate hallmarks of the defense program known as PAMP-triggered immunity (PTI). Interestingly, certain Salmonella strains carry mutations in the flg22 domain triggering PTI, suggesting that a strategy of Salmonella is to escape plant detection by mutating PAMP motifs. Another strategy may rely on the type III secretion system (T3SS) as T3SS mutants were found to induce stronger plant defense responses than wild type bacteria. Although Salmonella effector delivery into plant cells has not been shown, expression of Salmonella effectors in plant tissues shows that these bacteria also possess powerful means to manipulate the plant immune system. Altogether, the data gathered suggest that Salmonella triggers PTI in plants and evolved strategies to avoid or subvert plant immunity.